The Pandemic Policy U-Turn: Partisanship, Public Health, and Race in Decisions to Ease COVID-19 Social Distancing Policies in the United States. Issue 2 (1st June 2022) - Adolph, Christopher; Amano, Kenya; Bang-Jensen, Bree; Fullman, Nancy; Magistro, Beatrice; Reinke, Grace; Castellano, Rachel; Erickson, Megan; Wilkerson, John
Abstract : We explore the US states' evolving policy responses to the COVID-19 pandemic by examining governors' decisions to begin easing five types of social distancing policies after the initial case surge in March–April 2020. Applying event history models to original data on state COVID-19 policies, we test the relative influence of health, economic, and political considerations on their decisions. We find no evidence that differences in state economic conditions influenced when governors began easing. Governors of states with larger recent declines in COVID-19 deaths per capita and improving trends in new confirmed cases and test positivity were quicker to ease. However, politics played as powerful a role as epidemiological conditions, driven primarily by governors' party affiliation. Republican governors made the policy U-turn from imposing social distancing measures toward easing those measures a week earlier than Democratic governors, all else equal. Most troubling of all, we find that states with larger Black populations eased their social distancing policies more quickly, despite Black Americans' higher exposure to infection from SARS-CoV-2 and subsequent death from COVID-19.